Marketing global justice : the political economy of international criminal law / Christine Schwöbel-Patel. - Schwöbel-Patel, Christine (Cambridge studies in international and comparative law, 2021)
Marketing Global Justice is a critical study of efforts to 'sell' global justice. The book offers a new reading of the rise of international criminal law as the dominant institutional expression of global justice, linking it to the rise of branding. The political economy analysis employed highlights that a global elite benefit from marketised global justice whilst those who tend to be the 'faces' of global injustice - particularly victims of conflict - are instrumentalised and ultimately commodified. The book is an invitation to critically consider the predominance of market values in global justice, suggesting an 'occupying' of global justice as an avenue for drawing out social values.